Silver as Nishab Zakat to Improve Community Welfare in the Modern Era - Dwi Sartono; M Mahmudulhassan; Irfan Najmi; Saifuddin Amin; Muin Bensar (Walidem Institute and Publishing (WIP), 2023)
This study aims to analyze the zakat nishab of currency using the silver nishab or gold standard. Because so far most Indonesian people use Golden Nishob. Data collection was carried out using data from various references from trusted scholars' books. The method used in this study uses a normative-descriptive approach in a rational, empirical and systematic way. Based on the results of analysts, it was concluded that Nishab Zakat money is equated with silver worth 595 grams. Measuring money zakat nishab with silver zakat nishob is not arbitrary, but also refers to the opinions of authoritative scholars, because it will have a positive impact and benefit for the community, and can optimize the potential of Muslims to zakat to be more prospective and progressive.